2008
DOI: 10.1002/rcm.3579
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of iridoid glucosides by ultra‐performance liquid chromatography/electrospray ionization quadrupole time‐of‐flight tandem mass spectrometry

Abstract: The mass spectral fragmentation behavior of ten iridoid glucosides (IGs) has been studied using electrospray ionization (ESI), collision-induced dissociation (CID), and quadrupole time-of-flight tandem mass spectrometry (Q-TOF MS/MS). In the negative ESI mass spectra, the deprotonated [M-H](-) ion was observed for all of the ten IGs except gardoside methyl ester, while the formate adduct [M+HCOO](-) ion appeared to be favored by the presence of a methyl ester or a lactone group in the C-4 position when formic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 23 publications
4
56
0
Order By: Relevance
“…The product ion at m/z 121 was produced by the retro Diels-Alder (RDA) reaction from m/z 191. For 2, a high abundance [M+CH 3 COO]− ion was detected in negative ion mode, as reported previously [18]. It seemed that the [M+CH 3 COO]− ion was negligible when carboxyl was present.…”
Section: Structural Analysis Of Known Compounds 1-4supporting
confidence: 83%
See 1 more Smart Citation
“…The product ion at m/z 121 was produced by the retro Diels-Alder (RDA) reaction from m/z 191. For 2, a high abundance [M+CH 3 COO]− ion was detected in negative ion mode, as reported previously [18]. It seemed that the [M+CH 3 COO]− ion was negligible when carboxyl was present.…”
Section: Structural Analysis Of Known Compounds 1-4supporting
confidence: 83%
“…1), and was the main compound in the extract of P. scandens. Compound 2 may The molecular formula of compounds 3 was confirmed as C 18 H 24 O 12 , and the MS/MS spectrum of this compound was very similar to that of 1. This indicates that the skeleton structure of 3 is the same as that of 1, and the data suggested that the former may be asperulosidic acid (3) ( Fig.…”
Section: Structural Analysis Of Known Compounds 1-4mentioning
confidence: 83%
“…Therefore, the development of simple and rapid methods for the analysis of complex compositions is of great signifi cance in the quality control of herbal medicine. Nowadays, high-performance liquid chromatography (HPLC) coupled with mass spectrometry (MS) has been proved to be a very useful tool applied to the characterization of constituents in medicinal herbs (Qi et al, 2008;Li et al, 2008;Es-Safi et al, 2007). The systematic structural characterization of the compounds in Radix Scrophulariae with mass spectrometric method has, to our knowledge, not been examined, and is thus interesting from a phytochemical and analytical point of view.…”
Section: The Isolation and Identifi Cation Of Igs And Pgs In Radixmentioning
confidence: 98%
“…7). The MS/MS fragmentation network was generated after extracting the m/z values of the MS/MS product ions from the discriminatory features using MassHunter Qualitative Analysis Version 4 and visualized using Cytoscape, indicating product ion masses that had been previously reported from fragmentation of iridoid glycosides 110 .…”
mentioning
confidence: 99%